Analisis Penggunaan Microsoft 365 sebagai Media Pembelajaran Jarak Jauh MK Publik dan Kewirausahaan (Studi Kualitatif Kolaborasi antara STKIP PGRI Lumajang dan STKIP Bima) - Fidyah Jayatri; Dwi Yanuarindah Putri (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
The higher education process has changed rapidly; one of them is the emergence of the Independent State Learning program at the Merdeka Campus, where this program provides flexibility for students and lecturers to add insight and experience to see new circumstances, new places, through virtual activities. The purpose of this study is to understand more deeply the effectiveness of using Microsoft Teams as a distance learning medium during PJJ collaborative activities between STKIP PGRI Lumajang and STKIP Bima. The research method chosen is qualitative using a phenomenological approach. There were fourteen informants in this study. The key informants of this research were the Head of the Economic Education Study Program and Academic Advisory Lecturers and students who were members of the PJJ collaboration between STKIP PGRI Lumajang and STKIP Bima who took general courses and entrepreneurship. The results showed that STKIP PGRI Lumajang partner students could expand their knowledge and experience by participating in independent study programs at independent campuses. Students have the right to study outside the Main College. Students gain new knowledge outside the main campus. Students get new friends to exchange ideas outside of campus. Instructors focus more on teaching students by creating a creative learning environment. Dose shares his knowledge with students outside the main College. Lecturers have new insights about the condition of students outside their institutions.Keywords: Using Microsoft 365, Distance Learning Media